Speech aging: Production and perception. Issue 5 (2nd March 2021) - Tucker, Benjamin V.; Ford, Catherine; Hedges, Stephanie
Abstract: In this overview we describe literature on how speech production and speech perception change in healthy or normal aging across the adult lifespan. In the production section we review acoustic characteristics that have been investigated as potentially distinguishing younger and older adults. In the speech perception section studies concerning speaker age estimation and those investigating older listeners' perception are addressed. Our discussion focuses on major themes and other fruitful areas for future research. This article is categorized under: Linguistics > Language in Mind and Brain Linguistics > Linguistic Theory Psychology > Development and Aging Abstract : Summary figure illustrating the age ranges from a range of speech production studies.